Fatores associados com afeto negativo em indivíduos com e sem diagnóstico de fibromialgia - Sygel, Maurício (2024)
Fibromyalgia is a syndrome with high disabling potential, which affects around 10% of the population. Fibromyalgia encompasses chronic and generalized musculoskeletal pain and is a factor associated with several comorbidities. In addition, negative affect – a subjective condition of discomfort, mood swings, along with difficulties in experiencing positive aspects of life – has been explored in recent research on chronic diseases. International publications point to the urgent need for both prevention and intervention efforts for individuals with fibromyalgia, although there is a relative scarcity of data in Brazil. Therefore, the objective of this study was to evaluate the factors associated with negative affect in adults with and without a diagnosis of fibromyalgia. This is a cross sectional study. A convenience sample included 96 adults, with a mean age of 45.32 years (SD = 10.77), 48 (50%) of whom had fibromyalgia. The power of the study exceeded the 90% mark. Data collection took place online and included a sociodemographic questionnaire, in addition to the Depression, Anxiety and Stress Scales and the Kessler Scale. Data were analyzed using JASP program (version 0.19) and included descriptive and inferential statistical, such as means, standard deviations, frequencies and proportions, along with the X2 test, Fisher's exact test and comparisons techniques (i.e., t-test and Welch test). Logistic techniques were employed to understand the factors independently associated with negative affect. The logistic model indicated that the presence of comorbidities (OR: 4.26, 95%CI: 1.20 - 15.04) and diagnosis of fibromyalgia (OR: 4.88, 95%CI: 1.42 - 16.18) increased the changes in moderate, severe, and extremely severe symptoms of negative affect, while older age reduced the odds by 63% (OR: 0.27, 95%CI: 0.08 - 0.88). In sum, the data point to a robust association between fibromyalgia and clinically significant levels of negative affect, along with a higher number of comorbid conditions. Together, the findings corroborate previous investigations carried out with chronic patients, although, in the context of fibromyalgia, the present investigation appears to be the first to explore the outcome of negative affect, thus adding novelty, particularly in the Brazilian context. As implications, this study has the potential for health promotion and prevention actions, as well as applications in the scientific realm.